1990
DOI: 10.1111/j.1574-6968.1990.tb13971.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the capsule around mycobacteria grown in axenic media contains mycobacterial antigens: implications at the level of cell envelope architecture

Abstract: 1. Summary The intracellular growth of pathogenic mycobacteria has been linked to the presence of an electron transparent zone (ETZ or capsule), which surrounds the phagocytized bacteria and prevents the diffusion of lysosomal enzymes in infected macrophages. Recently, it was suggested that this capsule may be a bacterial structures, even being present in test tube‐grown pathogenic mycobacteria (FEMS Microbiol. Lett. 1988, 56, 225–230). In the present paper, we show that under special fixation and embedding co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, the rough variant can apparently synthesize a partially glycosylated lipopeptide that may be similar to the apolar GPL (3,48). The inhibitory nature of these drugs may also suggest a glycosylated component(s) that is shared by both the rough and smooth variants, perhaps as a part of the reported polysaccharide outer layer (37).…”
Section: Discussionmentioning
confidence: 99%
“…However, the rough variant can apparently synthesize a partially glycosylated lipopeptide that may be similar to the apolar GPL (3,48). The inhibitory nature of these drugs may also suggest a glycosylated component(s) that is shared by both the rough and smooth variants, perhaps as a part of the reported polysaccharide outer layer (37).…”
Section: Discussionmentioning
confidence: 99%
“…Adequate chemotherapy of these organisms is hampered, first, because of the multiple drug resistance, which has been attributed to an exclusion barrier localized in the cell wall (2,22), and, second, because of their particular mode of intracellular parasitism (20,21), implying that actively growing M. avium is not only surrounded by a capsule-like structure (28) but is also further protected inside the usually hostile phagosomal or phagolysosomal environment by its ability to inhibit normal macrophage functions (5,20,31).…”
Section: Discussionmentioning
confidence: 99%
“…Early reports suggested that the outer surface of mycobacteria was composed of mycosides (10,11). Later studies indicated the presence of an outer polysaccharide-rich layer (45, 50), which could explain the presence of the so-called electron-transparent zone often seen in electron micrographs of mycobacteria inside M (13, 18) and more recently in axenically grown bacteria (17,42,43,51). Support for this contention has come from studies describing the presence of an outer surface capsule on M. tuberculosis (12).…”
mentioning
confidence: 98%